TABULAR FORM OF REVISED SIMPLEX METHOD - Martha, Srinivas; B, Ravi Kumar (Journal of Global Research in Mathematical Archives(JGRMA), 2018)
The main purpose of this paper is to simplify the lengthy calculations in solving an LPP by the revised simplex method. For the easy understanding the illustrations have been incorporated along with the proposed algorithm.Â 